Waqf dan IbtidÃ„Â' dalam Mushaf Standar Indonesia dan Mushaf Madinah; Pengaruhnya terhadap Penafsiran - Badruddin, Ahmad (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
The experts of the Qur'an formulate and develop the theories about the Waqf and Ibtida’ which further are included in the Mushaf of the Quran with certain signs to make it easier for the readers of the Qur’an, especially for the foreigners (non-Arabic speaking people). The fact that exists is that there is a diversity of the sign of the stopping, particularly in the Indonesian standard manuscript and that of the Medina. Does it affect the interpretation? This paper tries to give an answer with the hope that this effort is expected to be the intellectual treasure that enriches the understanding of the people. Therefore, the confusion in some parts of society caused by this diversity can be overcome.Keywords : about the Waqf (stoppings) and Ibtida'(Beginnings), Indonesian standard manuscript and Medinan manuscript , diversity , intellectual treasure.